Biomechanical comparison of the femoral neck system versus InterTan nail and three cannulated screws for unstable Pauwels type III femoral neck fracture - Zheng Wang; Yong Yang; Gangning Feng; Haohui Guo; Zhirong Chen; Yaogeng Chen; Qunhua Jin (BioMedical Engineering OnLine, 2022)
Abstract Background There are a variety of internal fixation methods for unstable femoral neck fractures (FNFs), but the best method is still unclear. Femoral neck system (FNS) is a dynamic angular stabilization system with cross screws, and is a new internal fixation implant designed for minimally invasive fixation of FNFs. In this study, we conducted a biomechanical comparison of FNS, InterTan nail and three cannulated screws for the treatment of Pauwels III FNFs and investigate the biomechanical properties of FNS. Methods A total of 18 left artificial femurs were selected and randomly divide into Group A (fixation with FNS), Group B (fixation with InterTan nail) and Group C (fixation with three cannulated screws), with 6 specimens in each group. After creating Pauwels type III FNF models, the specimens in each were tested with non-destructive quasi-static tests, including torsion, A-P bending and axial compression tests. The average slope of the linear load–deformation curve obtained from quasi-static tests defines the initial torsional stiffness, A-P bending stiffness, and axial compression stiffness. After cyclic loading test was applied, the overall deformation of models and local deformation of implant holes in each group were assessed. The overall deformation was estimated as the displacement recorded by the software of the mechanical testing apparatus. Local deformation was defined as interfragmental displacement. Data were analyzed by one-way analysis of variance (ANOVA) followed by Bonferroni post hoc test using the SPSS software (version 24.0, IBM, New York, NY, USA). Correlation analysis was performed using Pearson’s correlation analysis. Results Group B exhibited significantly higher axial stiffness and A-P bending stiffness than the other two groups (P < 0.01), while Group A had significantly higher axial stiffness and A-P bending stiffness than Group C (P < 0.01). Groups A and B exhibited significantly higher torsional stiffness than Group C (P < 0.01), no statistical significance was observed between Groups A and B (P > 0.05). Group B exhibited significantly lower overall and local deformations than the other two groups (P < 0.01), while Group A had significantly lower overall and local deformations than Group C (P < 0.01). Correlation analysis revealed positive correlation between axial stiffness and A-P bending stiffness (r = 0.925, P < 0.01), torsional stiffness (r = 0.727, P < 0.01), between torsional stiffness and A-P bending stiffness; negative correlation between overall, local deformations and axial stiffness (r = − 0.889, − 0.901, respectively, both P < 0.01), and positive correlation between the two deformations (r = − 0.978, P < 0.01). Conclusion For fixation of unstable FNFs, InterTan nail showed the highest axial stiffness and A-P bending stiffness, followed by FNS, and then three cannulated screws. Torsional stiffness of FNS was comparable to that of the InterTan nail. FNS, as a novel minimally invasive implant, can create good mechanical environment for the healing of unstable FNFs. Clinical studies are needed to confirm the potential advantages of FNS observed in this biomechanical study.